Intravascular large B‐cell lymphoma presenting as Richter's syndrome with cerebral involvement in a patient with chronic lymphocytic leukemia. Issue 9 (20th July 2017) - Puckrin, Robert; Pop, Paula; Ghorab, Zeina; Keith, Julia; Chodirker, Lisa; Lin, Yulia; Callum, Jeannie
Key Clinical Message: Intravascular large B‐cell lymphoma (IVLBCL) is an aggressive non‐Hodgkin's lymphoma which can present with B symptoms, rash, and neurological deterioration. Up to 10% of cases of IVLBCL are associated with other hematological neoplasms, including this extremely rare presentation of IVLBCL as Richter's transformation in chronic lymphocytic leukemia. Abstract : Intravascular large B‐cell lymphoma (IVLBCL) is an aggressive non‐Hodgkin's lymphoma which can present with B symptoms, rash, and neurological deterioration. Up to 10% of cases of IVLBCL are associated with other hematological neoplasms, including this extremely rare presentation of IVLBCL as Richter's transformation in chronic lymphocytic leukemia.